Effect of joint-edge quality on mechanical properties of laser welded IN718 - Parchegani, Saeid; Piili, Heidi; Salminen, Antti (United Kingdom, 2026)
Studies on laser welding of metals have shown that the joint -edge quality such as surface roughness and geometry could influence the weld penetration and efficiency thus impacting its mechanical properties. In this study, laser welding was used to join IN718 sheet plates (3.2 mm in thickness) in a butt-joint configuration. The joint edges were prepared with two different methods of laser cutting and standard milling to investigate the effect ofjoint -edge quality on the mechanical properties of the weld. The laser-cut joints showed a larger fusion zone (FZ) area due to their higher surface roughness. The mechanical properties such as hardness, ultimate tensile strength (UTS), and yield strength were comparable regardless of the joint -edge differences. However, the laser-cut joint showed inferior fatigue strength, assessed at 106 cycles, due to micro cracks (microfissures) in the heat affected zone (HAZ).
20th Nordic Laser Materials Processing Conference